PERAHU PINCUK DARI GRESIK (SUMBANGAN PENGETAHUAN ETNOGRAFIS BAGI KHASANAH PERAHU NUSANTARA) - Hari Lelono (Berkala Arkeologi, 2010)
The history of the Indonesian Archipelago has demonstrated the glorious ages of large maritime kingdoms which governed this vast area, e.g Sriwijaya, Mataram Hindu, Singasari and Majapahit. During that age the maritime transportation must have been well developed and varieties of watercrafts might have been created to support interisland communication. Unfortunately, the hard evidence for this maritime technology are hardly recovered, so that our knowledge on watercraft construction technigue used at that time is very limited. In order to bridge that gap, ethnographic data may provide invaluable information to reconstruct the ancient maritime technology.One of the important information to reconstruct ancient watercraft building technigue are terms and names used for referring parts and components of the watercraft. Such information is still available among the traditional boat builder community in the village of Campurejo, near Gresik, East Java. Situated in the north coast of Java, Gresik had played a great role in the ancient maritime trade linking the eastem and western parts of the archipelago. Presumably, the traditional boat building technigue used here, as reflected in terminology for boat components, still represents the ancient Javanese boat technology. This paper describes the terms and construction method to build the unigue “pincuk” boat in Gresik area. These data will hopefully provide useful information to reconstruct ancient knowlegde on some aspects of maritime technology of Ancient Java